Contract law and social morality - Gerhart, Peter M. (Cambridge : Cambridge University Press, 2021)
When people in a relationship disagree about their obligations to each other, they need to rely on a method of reasoning that allows the relationship to flourish while advancing each person's private projects. This book presents a method of reasoning that reflects how people reason through disagreements and how courts create doctrine by reasoning about the obligations arising from the relationship. Built on the ideal of the other-regarding person, Contract Law and Social Morality displays a method of reasoning that allows one person to integrate their personal interests with the interests of another, determining how divergent interests can be balanced against each other. Called values-balancing reasoning, this methodology makes transparent the values at stake in a disagreement, and provides a neutral and objective way to identify and evaluate the trade-offs that are required if the relationship is to be sustained or terminated justly.
Introduction : understanding implied obligations : reasoning and methodology -- Individuals and relationships -- Authority's limits -- Promises and obligations -- Maximization and cooperation -- The foundations of value-balancing legal reasoning -- The scope of obligations -- The source of obligations -- Relationality redux : law on the ground and law on the books -- Legal enforceability : formation -- Performance obligations : methodological issues -- Performance obligations : the values-balancing approach -- Consumer contracts and standard terms -- Excused performance and risk allocation -- Remedies.
Title from publisher's bibliographic system (viewed on 08 Feb 2021).
Keywords: Contracts; Obligations (Law); Contracts -- Social aspects; Contracts -- Moral and ethical aspects; Standardized terms of contract